Ahogy az Isten elrendeli... - Olga filmje - Mohi, Sándor (Hungary : Dunatáj Alapítvány, 2000)
The black-and-white documentary shows the life of a gypsy community in Kászonújfalu through the fate of a young woman. We get to know the inner relationships, the emotional changes, the special relationship of life and death with the help of the special Dima Olga.
Romology Film Collection
Keywords: Documentary films